ANALISIS PEMBINAAN KEROHANIAN ISLAM DALAM MENINGKATKAN KUALITAS SIKAP DAN PERILAKU NARAPIDANA DI LEMBAGA PERMASYARAKATAN KELAS IIA CURUP - Agung Tri Sakti; Budi Priyatmono (Jurnal Komunikasi Hukum, 2024)
Law of the Republic of Indonesia Number 22 of 2022 emphasizes fair and humane treatment for prisoners in integrated coaching efforts, with the aim that they realize their mistakes, improve themselves, and prevent the repetition of criminal acts. Despite their limited space of movement, prisoners still feel inner pressure due to the unfulfilled desire for freedom, which can disrupt their mental and physical balance. Islamic spiritual development in correctional institutions plays an important role in improving the attitudes and behaviors of inmates, increasing religious awareness, strengthening moral values, and shaping characters such as self-control and responsibility. This study aims to analyze how the role of Islamic Spiritual Development can improve the quality of attitudes and behaviors of Class IIA Curup Prison Prisoners. This study uses a qualitative method, the analysis technique of this research consists of 3 stages consisting of: preparation stage, implementation stage, and report and evaluation stage (Sugiyono 2017), the data source in this study consists of primary data and secondary data. The results of the analysis show that the Islamic spiritual development program at the Class IIA Curup Prison has shown progressive results in improving and or improving the attitudes and behaviors of inmates. Managerial encouragement can increase the effectiveness and efficiency comprehensively towards improving the quality of inmates' attitudes and behaviors through Islamic spiritual development programs. Furthermore, stakeholders at the Curup Class IIA Prison must note how the role of each Islamic literacy development program in this study in influencing the improvement and/or change of attitudes and behaviors of inmates, by looking at the inhibiting factors and program proposals produced in this study. so that it can be overcome to lead to harmony and constructive synergy for the organization.